PENGEMBANGAN PARIWISATA PADA KAWASAN WISATA EQUATOR BONJOL KABUPATEN PASAMAN - Ana Ocsevani; Roni Ekha Putera; Desna Aromatica (UIR Press, 2024)
This thesis aims to describe how tourism development in the Equator Bonjol Tourism Area, Pasaman Regency. This research is motivated by the small number of visitors who come to the Equator Bonjol Tourism Area, while this tourism has the potential and has become a leading tourism that will be a reference for the development of tourism in other tourist attractions in Pasaman Regency. In addition, Pasaman Regency in its RPJMD sets Pasaman Tourism Destinations as one of the priority programs. Therefore, researchers are interested in describing how tourism development in the Equator Bonjol Tourism area. The method used in this study is a qualitative descriptive method using interview, observation and documentation data collection techniques. Then to test the validity of the data obtained in the field, it is carried out using the source triangulation technique. As well as for the selection of informants, researchers use purposive sampling techniques. Based on research that has been conducted on tourism development in the Equator Bonjol Tourism Area, it can be concluded that broadly speaking these 4 core components already exist but have not been maximized because there are still some parts of these components that are not yet available. The available ones also cannot be developed optimally because the management carried out is not good enough. So that the development of the Equator Bonjol Tourism Area needs to be addressed further.